Functional Blockade of E-Selectin in Tumor-Associated Vessels Enhances Anti-Tumor Effect of Doxorubicin in Breast Cancer - Morita, Yoshihiro (Cancers (Basel), 2020)
Chemotherapy is a mainstay of treatment for solid tumors. However, little is known about how therapy-induced immune cell infiltration may affect therapy response. We found substantial CD45(+) immune cell density adjacent to E-selectin expressing inflamed vessels in doxorubicin (DOX)-treated residual human breast tumors. While CD45 level was significantly elevated in DOX-treated wildtype mice, it remained unchanged in DOX-treated tumors from E-selectin null mice. Similarly, intravenous administration of anti-E-selectin aptamer (ESTA) resulted in a significant reduction in CD45(+) immune cell density in DOX-treated residual tumors, which coincided with a delay in tumor growth and lung metastasis in MMTV-pyMT mice. Additionally, both tumor infiltrating T-lymphocytes and tumor associated-macrophages were skewed towards T(H)2 in DOX-treated residual breast tumors; however, ESTA suppressed these changes. This study suggests that DOX treatment instigates de novo intratumoral infiltration of immune cells through E-selectin, and functional blockade of E-selectin may reduce residual tumor burden as well as metastasis through suppression of T(H)2 shift.